Optimalisasi Kesadaran Hukum Dalam Menanggulangi Petaka Ah Long Pada Buruh Migran Di PCIM Wilayah Kampung Baru Kuala Lumpur Malaysia - Wahyuni, Sri; Kusbandiyah, Ani; Wati, Ratna Kartika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2024)
Mitra is a member of PCIM Malaysia. According to observations and interviews with the chairman of PCIM Malaysia, you said that around 80-90% of PCIM Malaysia members are related to Ah Long. The aim of this activity is to provide solutions so that partners avoid being trapped by Ah Long, raise partners' awareness of the disaster of borrowing from Ah Long and provide skills and assistance in reporting Ah Long cases to the authorities. Activities carried out by the implementing team and partners are in the form of training and legal awareness assistance in overcoming the Ah Long disaster. This training and assistance is carried out comprehensively in accordance with the program so that this activity can provide partners with awareness of the Ah Long dangers and skills in dealing with the Ah Long dangers as well. ways to report the case to the authorities. IbM outputs are scientific articles that will be published in National Journals as mandatory outputs and Copyright as additional outputs.